Belimumab shows promise in neuropsychiatric lupus: Another challenge to find the offender - Shuilian Yu; Zhongjun Hou; Zhiping Liu; Zeying Lin; Ling Zhong; Qilin Yang; Wenhui Huang (Rheumatology & Autoimmunity, 2023)
Abstract Introduction Agents that can be used for the treatment of neuropsychiatric lupus (NPSLE) are lacking in the therapeutic armamentarium. Belimumab is a monoclonal antibody targeting the B‐cell activating factor (BAFF) and is approved by the US Food and Drug Administration as an additional treatment for systemic lupus erythematosus patients with persistent disease activity and lupus nephritis (LN); however, severe active central nervous system manifestations were excluded. Case Report We report on a treatment‐naïve LN patient with refractory NPSLE complicated with progressive posterior reversible encephalopathy syndrome (PRES) who was successfully treated via the combination of mycophenolate and belimumab, resulting in reversal of persistent headache and neuroradiologic manifestations. Conclusion Research on this topic could be relevant for identifying a possible correlation between BAFF and psychiatric NPSLE manifestations.